Humic acid interface modification material, perovskite solar cell and preparation method

By coating humic acid interface modification materials on the upper and lower interfaces of perovskite solar cells, the problem of defects in the buried interface of perovskite layer is solved, the photoelectric conversion efficiency and stability of the battery are improved, and more efficient pertitanium is achieved Mine battery performance.

CN119212531APending Publication Date: 2024-12-27JINGLING (NANJING) ELECTRIC POWER TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411333158.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

There are a large number of defects in perovskite solar cells, especially the buried interface of the perovskite layer, resulting in low non-radiative recombination and charge extraction efficiency. The existing research mainly focuses on modifying the upper interface, and there are few research on modifications to the lower interface, which affects the Battery stability and photoelectric conversion efficiency.

Method used

Using humic acid interface modification materials, the humic acid solution and aqueous solution are coated on the upper and lower interfaces of the perovskite absorbing layer, and the multi-hydroxy functional acid reacts with metal oxides or hydroxides to passivate interface defects and enhance The chemical stability and interface wetting of the material.

Benefits of technology

It effectively improves the photoelectric conversion efficiency and stability of perovskite batteries, and improves the overall performance of the battery by passivating interface defects and enhancing lead ion coordination.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119212531A_ABST
    Figure CN119212531A_ABST
Patent Text Reader

Abstract

The invention discloses a humic acid interface modification material, a perovskite solar cell and a preparation method, and the humic acid interface modification material adopts a humate solution with the concentration of 0.2-10 mg / ml and a humic acid aqueous solution with the concentration of 0.2-10 mg / ml, the interface modification material is coated on an electron transport layer / perovskite interface and a perovskite / hole transport layer interface to optimize the preparation process of the perovskite cell, the molecules of the interface modification material used in the preparation method carry functional groups containing oxygen anions, and the interface defects between perovskite and the transport layer can be passivated to improve the performance of the perovskite cell. And the interface wettability between the perovskite and the transmission layer is improved, so that the photoelectric conversion efficiency of the perovskite cell is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of perovskite photovoltaics, and in particular relates to a humic acid interface modification material, a perovskite solar cell and a preparation method thereof. Background Art

[0002] In perovskite solar cells (PSCs), the common "sandwich" structure consists of a perovskite light absorption layer (PVK), a hole transport layer (HTL) and an electron transport layer (ETL). The interface contact between these layers has a direct impact on the performance and stability of the device. There are a large number of deep energy level defects at the interface, which will affect the transport of photogenerated carriers and the migration of perovskite ions, thereby inducing non-radiative recombination and reducing the photoelectric conversion efficiency of the battery. Modification and adjustment of the interface is one of the important methods to overcome these negative effects. Current research mainly focuses on methods to modify the upper surface of the perovskite light absorption layer, by passivating surface defects to inhibit non-radiative recombination, promote interfacial charge extraction, and enhance the stability of the perovskite film. However, there are few studies on the modification of the lower surface of the perovskite layer (buried interface), because the bottom interface of the perovskite is difficult to expose and the related mechanism research is relatively difficult. In fact, there are also a large number of defects in the buried interface of the perovskite layer, and the passivation of these defects is also crucial to achieve efficient and stable battery devices. Therefore, finding suitable interface modification materials and modifying the upper and lower interfaces of the perovskite light-absorbing layer is a new idea for optimizing the production process of perovskite cells. Summary of the invention

[0003] In view of the above technical problems, the primary purpose of the present invention is to provide a humic acid interface modification material for the preparation of perovskite solar cells, which plays an important role in improving the photoelectric conversion efficiency of perovskite cells.

[0004] The second object of the present invention is to provide a perovskite solar cell prepared by an interface modification method and a preparation method thereof, wherein the photoelectric conversion efficiency of the perovskite solar cell can be improved by introducing the interface modification material into the electron transport layer / perovskite light absorbing layer interface and the hole transport layer / perovskite light absorbing layer interface.

[0005] To achieve the above object, the technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a humic acid interface modification material, which is coated on the upper and lower interfaces of a perovskite light-absorbing layer of a perovskite solar cell; the humic acid interface modification material comprises a humate solution with a concentration of 0.2-10 mg / ml and a humic acid aqueous solution with a concentration of 0.2-10 mg / ml; the humate solution with a concentration of 0.2-10 mg / ml is coated on a substrate at the lower interface of the perovskite light-absorbing layer; the humic acid aqueous solution with a concentration of 0.2-10 mg / ml is coated on the upper interface of the perovskite light-absorbing layer.

[0006] Preferably, the humate solution is: It is obtained by dissolving humic acid and metal oxide or hydroxide in a polar solution and reacting them; The metal oxide or hydroxide is one of potassium hydroxide, sodium hydroxide, zinc oxide and magnesium oxide; When used for a formal structured perovskite solar cell, the polar solution is one of water, ethanol solution, isopropanol solution, n-butanol solution and dimethyl sulfoxide solution; When used for a perovskite solar cell with an inverted structure, the polar solution is one of an ethanol solution, an isopropanol solution, an n-butanol solution and a dimethyl sulfoxide solution; The humic acid aqueous solution is obtained by dissolving humic acid in water.

[0007] In a second aspect, the present invention provides a perovskite solar cell, comprising a conductive glass substrate, a carrier transport layer, a perovskite light absorbing layer and a back electrode, wherein an interface modification layer is assembled on the upper interface and the lower interface of the perovskite light absorbing layer, and the interface modification layer is prepared using a humic acid interface modification material, and the humic acid interface modification material is the above-mentioned humic acid interface modification material.

[0008] In a third aspect, the present invention provides a method for preparing a perovskite solar cell with a formal structure, comprising: Assembling an electron transport layer on the surface of the conductive glass; A humate solution is coated on the surface of the electron transport layer to form a lower interface modification layer; the humate solution is the above-mentioned humate solution; Assembling a perovskite light-absorbing layer on the surface of the lower interface modification layer, and coating a humic acid aqueous solution on the surface of the perovskite light-absorbing layer to form an upper interface modification layer; the humic acid aqueous solution is the above-mentioned humic acid aqueous solution; A hole transport layer and a back electrode are assembled on the surface of the upper interface modification layer.

[0009] Preferably, The electron transport layer includes tin dioxide, titanium dioxide, zinc oxide, tungsten oxide, molybdenum oxide and a composite thereof; The hole transport layer is made of poly 3-hexylthiophene or 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene.

[0010] Preferably, the coating of the humate solution comprises: Dissolving humic acid and metal oxide or hydroxide in a polar solution to obtain a humate solution with a concentration of 0.2-10 mg / ml, and spin coating the solution on the substrate at a speed of 2000-5000 r / min for 20-60 s; The metal oxide or hydroxide is one of potassium hydroxide, sodium hydroxide, zinc oxide and magnesium oxide; The polar solution is one of water, ethanol solution, isopropanol solution and n-butanol solution; The coating of humic acid aqueous solution comprises: A humic acid aqueous solution with a concentration of 0.2-10 mg / ml is obtained and spin-coated on the surface of the perovskite light-absorbing layer at a speed of 2000-5000 r / min for 20-60 s.

[0011] In a fourth aspect, the present invention provides a method for preparing an inverted perovskite solar cell, comprising: Assembling a hole transport layer or SAM layer on the surface of the conductive glass; Coating a humate solution on the surface of the hole transport layer or the SAM layer to form a lower interface modification layer; the humate solution is the above-mentioned humate solution; Assembling a perovskite light-absorbing layer on the surface of the lower interface modification layer, and coating a humic acid aqueous solution on the surface of the perovskite light-absorbing layer to form an upper interface modification layer; the humic acid aqueous solution is the above-mentioned humic acid aqueous solution; An electron transport layer and a back electrode are assembled on the surface of the upper interface modification layer.

[0012] Preferably, the hole transport layer is made of one of polynickel oxide, cuprous oxide, cuprous sulfide, cuprous thiocyanate and cuprous iodide; The SAM layer adopts one of [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid, [2-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphonic acid, [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid, [4-(9H-carbazole-9-yl)butyl]phosphonic acid, [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid and [2-(9H-carbazole-9-yl)ethyl]phosphonic acid; The electron transport layer adopts one of [6,6]-phenyl C61 butyric acid methyl ester, [6,6]-phenyl C71 butyric acid methyl ester and footballene.

[0013] Preferably, the coating of the humate solution comprises: Dissolving humic acid and metal oxide or hydroxide in a polar solution to obtain a humate solution with a concentration of 0.2-10 mg / ml, and spin coating the solution on the substrate at a speed of 2000-5000 r / min for 20-60 s; The metal oxide or hydroxide is one of potassium hydroxide, sodium hydroxide, zinc oxide and magnesium oxide; The polar solution is one of an ethanol solution, an isopropanol solution, a n-butanol solution and a dimethyl sulfoxide solution; The coating of humic acid aqueous solution comprises: A humic acid aqueous solution with a concentration of 0.2-10 mg / ml is obtained and spin-coated on the surface of the perovskite light-absorbing layer at a speed of 2000-5000 r / min for 20-60 s.

[0014] Preferably, the perovskite light-absorbing layer includes methylamine lead iodine, formamidine lead iodine, methylamine lead bromide, formamidine lead bromide, cesium lead iodine, cesium lead bromide, methylamine tin iodine, methylamine tin bromide and a composite thereof.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a humic acid interface modification material, a perovskite solar cell and a preparation method. A humate solution is used as an interface modification material. The interface modification material has polyhydroxyl groups in its molecules, which can react with oxides and hydroxides of active metals to generate organic acid salts. The organic acid is easily adsorbed on the oxygen defect surface of the metal oxide crystal, which plays a role in passivating interface defects and improving interface wettability. In addition, the organic acid used in the present invention is easy to coordinate with lead ions, enhance the chemical stability of the perovskite material, and ultimately improve the comprehensive performance of the perovskite battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The structural diagram of the formal perovskite battery prepared by the present invention; Figure 2 A structural diagram of an inverse perovskite battery prepared by the present invention; Figure 3 This is a statistical chart of the photoelectric conversion efficiency of the perovskite cells prepared in Example 1, Example 2, Example 3 and Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0017] Here, exemplary embodiments are described in detail, and examples thereof are shown in the accompanying drawings. When the following description refers to the drawings, unless otherwise indicated, the same numbers in different drawings represent the same or similar elements. The implementations described in the following exemplary embodiments do not represent all implementations consistent with the present application.

[0018] The terms used in this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.

[0019] If the specific conditions are not specified in the embodiments of the present invention, the conditions are carried out according to conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be obtained by conventional technical means or obtained commercially. The technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians of the art without making creative work are within the scope of protection of the present invention.

[0020] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] It should be noted that, in the absence of conflict, the features in the following embodiments and implementations may be combined with each other.

[0022] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be obtained by conventional technical means or purchased commercially.

[0023] In a first aspect, the present invention provides a humic acid interface modification material, which is coated on the upper interface and the lower interface of the perovskite light absorbing layer of a perovskite solar cell, namely, the electron transport layer / perovskite light absorbing layer interface and the perovskite light absorbing layer / hole transport layer interface, and the humic acid interface modification material comprises a humic acid metal solution with a concentration of 0.2-10 mg / ml and a humic acid aqueous solution with a concentration of 0.2-10 mg / ml.

[0024] Specifically, a humate solution with a concentration of 0.2-10 mg / ml is coated on the substrate at the lower interface of the perovskite light-absorbing layer; and a humic acid aqueous solution with a concentration of 0.2-10 mg / ml is coated on the upper interface of the perovskite light-absorbing layer.

[0025] In the present invention, the humate solution is obtained by dissolving humic acid and metal oxide or hydroxide in a polar solution for reaction.

[0026] Specifically, the metal oxide or hydroxide is one of potassium hydroxide, sodium hydroxide, zinc oxide and magnesium oxide; When used in a formal structure perovskite solar cell, the polar solution is one of water, ethanol, isopropanol, n-butanol and dimethyl sulfoxide. When used for inverse-structured perovskite solar cells, the polar solution is one of an ethanol solution, an isopropanol solution, an n-butanol solution and a dimethyl sulfoxide solution.

[0027] In a second aspect, the present invention provides a perovskite solar cell, comprising a conductive glass substrate, a carrier transport layer, a perovskite light absorbing layer and a back electrode, wherein an interface modification layer is assembled on the upper interface and the lower interface of the perovskite light absorbing layer, and the interface modification layer is prepared using a humic acid interface modification material, and the humic acid interface modification material is the above-provided humate solution with a concentration of 0.2-10 mg / ml and the humic acid aqueous solution with a concentration of 0.2-10 mg / ml.

[0028] In a third aspect, the present invention provides a method for preparing a perovskite solar cell with a formal structure, the preparation process being: Step 1: ultrasonically clean the conductive glass substrate in deionized water, acetone and ethanol solutions in sequence, dry it with nitrogen, and then treat it in a UV ozone cleaning machine for 10-30 minutes, and assemble the electron transport layer on the surface of the substrate by coating or evaporation; Step 2: Dissolve humic acid (CAS No.: 1415-93-6) and potassium hydroxide in water to obtain a potassium humate aqueous solution with a concentration of 0.2-10 mg / ml, and spin-coat the solution on the substrate at a speed of 2000-5000 r / min for 20-60 s; Step 3: Assemble a perovskite light-absorbing layer on the surface of the substrate, and spin-coat a humic acid solution with a concentration of 0.2-10 mg / ml on the surface of the perovskite light-absorbing layer at a speed of 2000-5000 r / min for 20-60 s; Step 4: Assemble the hole transport layer and the back electrode in sequence on the substrate surface.

[0029] Preferably, the electron transport layer in step 1 comprises one of tin dioxide, titanium dioxide, zinc oxide, tungsten oxide, molybdenum oxide or a composite thereof.

[0030] Preferably, the potassium hydroxide in step 2 can be replaced by sodium hydroxide, zinc oxide, and magnesium oxide, and accordingly, sodium humate, zinc humate, and magnesium humate are obtained.

[0031] Preferably, the aqueous solution in step 2 can be replaced by a solution composed of polar solvents such as ethanol solution, isopropanol solution, and n-butanol solution.

[0032] Preferably, the perovskite light-absorbing layer in step 3 includes but is not limited to methylamine lead iodine (MAPbI3), formamidine lead iodine (FAPbI3), methylamine lead bromide (MAPbBr3), formamidine lead bromide (FAPbBr3), cesium lead iodine (CsPbI3), cesium lead bromide (CsPbBr3), methylamine tin iodine (MASnI3), methylamine tin bromide (MASnBr3) and their composites.

[0033] Preferably, the hole transport layer in step 4 includes, but is not limited to, poly 3-hexylthiophene (P3HT), 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (Spiro-OMeTAD).

[0034] In a fourth aspect, the present invention provides a method for preparing a trans-structured perovskite solar cell, the preparation process comprising: Step 1: ultrasonically clean the conductive glass substrate in deionized water, acetone and ethanol solutions in sequence, dry it with nitrogen, and then treat it in a UV ozone cleaning machine for 10-30 min, and assemble a hole transport layer or a SAM layer on the surface of the substrate by coating or evaporation; Step 2: dissolving humic acid and potassium hydroxide in ethanol to obtain a potassium humate ethanol solution with a concentration of 0.2-10 mg / ml, and spin coating the solution on the substrate at a speed of 2000-5000 r / min for 20-60 s; Step 3: Assemble a perovskite light-absorbing layer on the surface of the substrate, and spin-coat a humic acid solution with a concentration of 0.2-10 mg / ml on the surface of the perovskite light-absorbing layer at a speed of 2000-5000 r / min for 20-60 s; Step 4: Assemble the hole transport layer and the back electrode in sequence on the substrate surface.

[0035] Preferably, the hole transport layer in step 1 includes polynickel oxide, cuprous oxide, cuprous sulfide, cuprous thiocyanate and cuprous iodide; the SAM layer includes [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid (Me-4PACz), [2-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphonic acid (Me-2PACz), [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid (MeO-4PACz), [4-(9H-carbazole-9-yl)butyl]phosphonic acid (4PACz), [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid (MeO-2PACz), [2-(9H-carbazole-9-yl)ethyl]phosphonic acid (2PACz), etc.

[0036] Preferably, the potassium hydroxide in step 2 can be replaced by one or more of sodium hydroxide, zinc oxide, and magnesium oxide, and accordingly, one or more of sodium humate, zinc humate, and magnesium humate are obtained.

[0037] Preferably, the ethanol solution in step 2 can be replaced by isopropanol solution, n-butanol solution, dimethyl sulfoxide solution, etc.

[0038] Preferably, the perovskite light-absorbing layer in step 3 includes but is not limited to methylamine lead iodine (MAPbI3), formamidine lead iodine (FAPbI3), methylamine lead bromide (MAPbBr3), formamidine lead bromide (FAPbBr3), cesium lead iodine (CsPbI3), cesium lead bromide (CsPbBr3), methylamine tin iodine (MASnI3), methylamine tin bromide (MASnBr3) and their composites.

[0039] Preferably, the electron transport layer in step 4 comprises [6,6]-phenyl C61 butyric acid methyl ester (PC 61 BM)、[6,6]-phenyl C71 butyric acid methyl ester(PC 71 BM) and sphericalene (C 60 )wait.

[0040] The above preparation method is used to prepare a regular structure perovskite solar cell and a transverse structure perovskite solar cell, and their performance is tested and compared with the performance of a perovskite solar cell without an interface modification layer. Example 1

[0041] The ITO conductive glass was ultrasonically cleaned in deionized water, acetone and ethanol solutions in sequence, dried with nitrogen and then treated in a UV ozone cleaner for 10 min. The SnO2 nanocolloid solution was spin-coated on the surface of the ITO glass and annealed on a hot plate at 150 °C for 0.5 h to obtain a SnO2 electron transport layer.

[0042] Humic acid and potassium hydroxide were dissolved in water at a molar ratio of 1:2 to obtain a potassium humate aqueous solution with a concentration of 0.5 mg / ml. 50 μl of the potassium humate aqueous solution was spin-coated on the substrate surface at a speed of 3000 r / min for 40 s to obtain a lower interface modification layer.

[0043] Equimolar amounts of MAI and PbI2 were dissolved in dimethyl sulfoxide (DMSO) to form a solution with a concentration of 1 mol / L, and the solution was spin-coated on the substrate surface. The speed of the coating machine was set to 3000 r / min. After spinning for 25 seconds, 50 μl of chlorobenzene was dropped on the center of the perovskite substrate. After spin coating at 3000 r / min for 10 seconds, the ITO glass was placed on a hot plate at 120 °C and heated for 10 minutes to obtain a perovskite light-absorbing layer.

[0044] 50 μl of 1 mg / ml humic acid aqueous solution was spin-coated on the substrate surface at a speed of 3000 r / min for 30 seconds to obtain an upper interface modification layer.

[0045] An acetonitrile solution containing 4-tert-butylpyridine (tBP) and Li-TFSI was mixed with a chlorobenzene solution of Spiro-OMeTAD and spin-coated on the perovskite light-absorbing layer substrate as a hole transport layer.

[0046] Finally, the substrate was placed in an evaporator and an 80 nm gold film was evaporated as the back electrode to prepare a formal structure of a perovskite solar cell, such as Figure 1 shown. Example 2

[0047] The ITO glass was ultrasonically cleaned in deionized water, acetone and ethanol solutions in sequence, dried with nitrogen and then treated in a UV ozone cleaner for 20 min. An aqueous solution containing Sn salt colloid was spin-coated on the surface of the ITO glass and annealed on a hot stage at 180 °C for 30 min to obtain a SnO2 electron transport layer.

[0048] Humic acid and sodium hydroxide were dissolved in water at a molar ratio of 1:2 to obtain a sodium humate aqueous solution with a concentration of 0.5 mg / ml. 50 μl of the sodium humate aqueous solution was spin-coated on the substrate surface at a speed of 3000 r / min for 30 s to obtain a lower interface modification layer.

[0049] Equimolar amounts of FAI and PbI2 were dissolved in DMSO to form a solution with a concentration of 1.5 mol / L, and then spin-coated on the substrate surface. The speed of the coating machine was set to 3000 r / min, and after drying for 15 seconds, 80 μL of chlorobenzene was dropped on the center of the perovskite substrate. After spin coating at 3000 r / min for 30 seconds, the ITO glass was placed on a 130 ℃ hot stage and heated for 10 minutes to obtain a perovskite light-absorbing layer.

[0050] 50 μl of 1.5 mg / ml humic acid aqueous solution was spin-coated on the substrate surface at a speed of 4000 r / min for 30 s to obtain an upper interface modification layer.

[0051] An acetonitrile solution containing 4-tert-butylpyridine (tBP) and Li-TFSI was mixed with a chlorobenzene solution of Spiro-OMeTAD and spin-coated on a perovskite substrate as a hole transport layer.

[0052] Finally, the substrate was placed in an evaporator and a 70 nm gold film was evaporated as the back electrode to prepare a formal structured perovskite solar cell. Example 3

[0053] The ITO glass was ultrasonically cleaned in deionized water, acetone and ethanol solutions in sequence, dried with nitrogen and then treated in a UV ozone cleaner for 20 min. The SnO2 nanocolloid solution was spin-coated on the surface of the ITO glass and annealed on a hot stage at 140 °C for 40 min to obtain a SnO2 electron transport layer.

[0054] Equimolar amounts of humic acid and magnesium oxide were dissolved in water to obtain a 1 mg / ml magnesium humate solution. 60 μl of the magnesium humate solution was spin-coated on the substrate surface at a speed of 3500 r / min for 25 s to obtain a lower interface modification layer.

[0055] MAPbI3 was dissolved in sulfolane to form a uniform solution with a concentration of 1.3 mol / L, and then spin-coated on the substrate surface. The spin coater speed was set to 3000 r / min, and after drying for 30 seconds, 80 μl of ethyl acetate was dropped on the center of the perovskite substrate. After spin coating at 3500 r / min for 20 seconds, the ITO glass was placed on a 110 ℃ hot stage and heated for 12 minutes to obtain the perovskite light-absorbing layer.

[0056] 60 μl of 2 mg / ml humic acid aqueous solution was spin-coated on the substrate surface at a speed of 4500 r / min for 40 s to obtain an upper interface modification layer.

[0057] An acetonitrile solution containing 4-tert-butylpyridine (tBP) and Li-TFSI was mixed with a chlorobenzene solution of Spiro-OMeTAD and spin-coated on a perovskite substrate as a hole transport layer.

[0058] Finally, the substrate was placed in a magnetron sputtering instrument, and an 80 nm silver film was vacuum sputtered as the back electrode to prepare a formal structured perovskite solar cell. Example 4

[0059] The ITO glass was ultrasonically cleaned in deionized water, acetone and ethanol solutions in sequence, dried with nitrogen and treated in a UV ozone cleaner for 20 min. The ethanol solution containing MeO-2PACz was spin-coated on the ITO glass surface and annealed on a 110 °C hot plate for 15 min to obtain a SAM layer.

[0060] Humic acid and sodium hydroxide were dissolved in ethanol at a molar ratio of 1:2 to obtain a sodium humate ethanol solution with a concentration of 0.5 mg / ml. 90 μl of the sodium humate ethanol solution was spin-coated on the substrate surface at a speed of 3000 r / min for 25 s to obtain a lower interface modification layer.

[0061] FAPbI3 and CsPbBr3 were dissolved in a mixed solvent of DMF and DMSO (the molar ratio of DMF to DMSO was 1:4) at a molar ratio of 15:1 to form a uniform solution with a total molar weight of 1.5 mol / L, and then spin-coated on the substrate surface. The speed of the coater was set to 3000 r / min. After drying for 25 seconds, 80 μL of chlorobenzene solution was dropped on the center of the perovskite substrate. After spin coating at 3000 r / min for 15 seconds, the ITO glass was placed on a hot plate at 110 °C and heated for 10 minutes to obtain a perovskite light-absorbing layer.

[0062] 70 μl of 1.0 mg / ml humic acid aqueous solution was spin-coated on the substrate surface at a speed of 5000 r / min for 30 s to obtain an upper interface modification layer.

[0063] A chlorobenzene solution containing PC61BM was spin-coated on the perovskite substrate as an electron transport layer.

[0064] Finally, the substrate was placed in a magnetron sputtering instrument and a 100 nm silver film was vacuum sputtered as the back electrode to prepare a transverse structure perovskite solar cell, such as Figure 2 shown. Example 5

[0065] The ITO glass was ultrasonically cleaned in deionized water, acetone and ethanol solutions in sequence, dried with nitrogen, and then treated in a UV ozone cleaner for 25 min. A uniform solution of water and isopropanol (molar ratio of water to isopropanol was 4:1) containing polynickel oxide was spin-coated on the surface of the ITO glass and annealed on a 180 °C hot plate for 30 min to obtain a hole transport layer.

[0066] Equimolar amounts of humic acid and zinc oxide were dissolved in water to obtain a humic acid zinc solution with a concentration of 1 mg / ml. 60 μl of the humic acid zinc aqueous solution was spin-coated on the substrate surface at a speed of 3500 r / min for 25 s to obtain a lower interface modification layer.

[0067] FAPbIr3 and CsPbI3 were dissolved in a mixed solvent of DMF and DMSO (the molar ratio of DMF to DMSO was 1:4) at a molar ratio of 12:1 to form a uniform solution with a total molar weight of 1.4 mol / L. The solution was then spin-coated on the substrate surface, the speed of the coating machine was set to 4000 r / min, and after drying for 25 seconds, 120 μL of chlorobenzene solution was dropped on the center of the perovskite substrate. After spin coating at 4000 r / min for 15 seconds, the ITO glass was placed on a 150 °C hot plate and heated for 15 minutes to obtain a perovskite light-absorbing layer.

[0068] 70 μl of 1.5 mg / ml humic acid aqueous solution was spin-coated on the substrate surface at a speed of 4500 r / min for 35 s to obtain an upper interface modification layer.

[0069] A chlorobenzene solution containing PC61BM was spin-coated on the perovskite substrate as an electron transport layer.

[0070] Finally, the substrate was placed in a magnetron sputtering instrument, and an 80 nm silver film was vacuum sputtered as the back electrode to prepare an inverted perovskite solar cell.

[0071] Comparative Example 1 (without interface modification layer) Comparative Example 1 is a comparative example of the above-mentioned Example 1, except that no interface modification layer is assembled on the upper and lower interfaces of the perovskite light-absorbing layer of Comparative Example 1, and the rest of the preparation process is the same as that of the above-mentioned Example 1, and the preparation process is as follows: The ITO glass was ultrasonically cleaned in deionized water, acetone and ethanol solutions in sequence, dried with nitrogen and then treated in a UV ozone cleaner for 10 min. The SnO2 nanocolloid solution was spin-coated on the surface of the ITO glass and annealed on a 150 °C hot stage for 0.5 h to obtain a SnO2 electron transport layer.

[0072] Equimolar amounts of MAI and PbI2 were dissolved in DMSO to form a solution with a concentration of 1 mol / L, and the solution was spin-coated on the substrate surface. The speed of the coating machine was set to 3000 r / min. After drying for 25 seconds, 50 μl of chlorobenzene was dropped on the center of the perovskite substrate. After spin coating at 3000 r / min for 10 seconds, the ITO glass was placed on a hot plate at 120 °C and heated for 10 minutes to obtain a perovskite light-absorbing layer.

[0073] An acetonitrile solution containing 4-tert-butylpyridine (tBP) and Li-TFSI was mixed with a chlorobenzene solution of Spiro-OMeTAD and spin-coated on a perovskite substrate as a hole transport layer.

[0074] Finally, the substrate was placed in an evaporator and an 80 nm gold film was evaporated as the back electrode.

[0075] The perovskite solar cells prepared in the above-mentioned Examples 1 to 3 and Comparative Example 1 were tested to obtain the IV test curves of the prepared perovskite solar cells and calculate the photoelectric conversion efficiency. Figure 3 It can be seen that the efficiency of the cells prepared in Examples 1-3 is significantly higher than that in Comparative Example 1. Therefore, the use of the bottom-burying modification method provided by the present invention to prepare perovskite cells can improve the photoelectric conversion efficiency of the cells.

[0076] Those skilled in the art will readily appreciate other embodiments of the present application after considering the specification and practicing the contents disclosed herein. The present application is intended to cover any variations, uses or adaptations of the present application, which follow the general principles of the present application and include common knowledge or customary technical means in the art that are not disclosed in the present application.

[0077] It should be understood that the present application is not limited to the exact construction that has been described above and shown in the drawings, and that various modifications and changes may be made without departing from the scope thereof.

Claims

1. A humic acid interface modification material, characterized in that: The humic acid interface modification material is coated on the upper and lower interfaces of the perovskite light-absorbing layer of the perovskite solar cell; the humic acid interface modification material comprises a humate solution with a concentration of 0.2-10 mg / ml and a humic acid aqueous solution with a concentration of 0.2-10 mg / ml; the humate solution with a concentration of 0.2-10 mg / ml is coated on the substrate at the lower interface of the perovskite light-absorbing layer; the humic acid aqueous solution with a concentration of 0.2-10 mg / ml is coated on the upper interface of the perovskite light-absorbing layer.

2. A humic acid interface modification material according to claim 1, characterized in that: The humate solution is: It is obtained by reacting humic acid with metal oxide or metal hydroxide in a polar solvent; The metal oxide or metal hydroxide is one of potassium hydroxide, sodium hydroxide, zinc oxide and magnesium oxide; When used for a formal structured perovskite solar cell, the polar solution is one of water, ethanol solution, isopropanol solution, n-butanol solution and dimethyl sulfoxide solution; When used for a perovskite solar cell with an inverted structure, the polar solution is one of an ethanol solution, an isopropanol solution, an n-butanol solution and a dimethyl sulfoxide solution; The humic acid aqueous solution is obtained by dissolving humic acid in water.

3. A perovskite solar cell, comprising a conductive glass substrate, a carrier transport layer, a perovskite light absorbing layer and a back electrode, characterized in that: An interface modification layer is assembled on both the upper interface and the lower interface of the perovskite light absorbing layer. The interface modification layer is prepared by using a humic acid interface modification material. The humic acid interface modification material is the humic acid interface modification material according to any one of claims 1 to 2.

4. A method for preparing a perovskite solar cell, characterized in that: include: Assembling an electron transport layer on the surface of the conductive glass; coating a humate solution on the surface of the electron transport layer to form a lower interface modification layer; The humate solution is the humate solution according to any one of claims 1 to 2; Assembling a perovskite light-absorbing layer on the surface of the lower interface modification layer, and coating a humic acid aqueous solution on the surface of the perovskite light-absorbing layer to form an upper interface modification layer; the humic acid aqueous solution is the humic acid aqueous solution according to any one of claims 1 to 2; A hole transport layer and a back electrode are assembled on the surface of the upper interface modification layer.

5. The method for preparing a perovskite solar cell according to claim 4, characterized in that: The electron transport layer includes tin dioxide, titanium dioxide, zinc oxide, tungsten oxide, molybdenum oxide and a composite thereof; The hole transport layer is made of poly 3-hexylthiophene or 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene.

6. The method for preparing a perovskite solar cell according to claim 5, characterized in that: The coating of humate solution comprises: Dissolving humic acid and metal oxide or hydroxide in a polar solution to obtain a humate solution with a concentration of 0.2-10 mg / ml, and spin coating the solution on the substrate at a speed of 2000-5000 r / min for 20-60 s; The metal oxide or hydroxide is one of potassium hydroxide, sodium hydroxide, zinc oxide and magnesium oxide; The polar solution is one of water, ethanol solution, isopropanol solution and n-butanol solution; The coating of humic acid aqueous solution comprises: A humic acid aqueous solution with a concentration of 0.2-10 mg / ml is obtained and spin-coated on the surface of the perovskite light-absorbing layer at a speed of 2000-5000 r / min for 20-60 s.

7. A method for preparing a perovskite solar cell, characterized in that: include: Assembling a hole transport layer or SAM layer on the surface of the conductive glass; coating a humate solution on the surface of the hole transport layer or the SAM layer to form a lower interface modification layer; The humate solution is the humate solution according to any one of claims 1 to 2; Assembling a perovskite light-absorbing layer on the surface of the lower interface modification layer, and coating a humic acid aqueous solution on the surface of the perovskite light-absorbing layer to form an upper interface modification layer; the humic acid aqueous solution is the humic acid aqueous solution according to any one of claims 1 to 2; An electron transport layer and a back electrode are assembled on the surface of the upper interface modification layer.

8. The method for preparing a perovskite solar cell according to claim 7, characterized in that: The hole transport layer is made of one of polynickel oxide, cuprous oxide, cuprous sulfide, cuprous thiocyanate and cuprous iodide; The SAM layer adopts one of [4-(3,6-dimethyl-9H-carbazole-9-yl)butyl]phosphonic acid, [2-(3,6-dimethyl-9H-carbazole-9-yl)ethyl]phosphonic acid, [4-(3,6-dimethoxy-9H-carbazole-9-yl)butyl]phosphonic acid, [4-(9H-carbazole-9-yl)butyl]phosphonic acid, [2-(3,6-dimethoxy-9H-carbazole-9-yl)ethyl]phosphonic acid and [2-(9H-carbazole-9-yl)ethyl]phosphonic acid; The electron transport layer adopts one of [6,6]-phenyl C61 butyric acid methyl ester, [6,6]-phenyl C71 butyric acid methyl ester and footballene.

9. The method for preparing a perovskite solar cell according to claim 7, characterized in that: The coating of humate solution comprises: Dissolving humic acid and metal oxide or hydroxide in a polar solution to obtain a humate solution with a concentration of 0.2-10 mg / ml, and spin coating the solution on the substrate at a speed of 2000-5000 r / min for 20-60 s; The metal oxide or hydroxide is one of potassium hydroxide, sodium hydroxide, zinc oxide and magnesium oxide; The polar solution is one of an ethanol solution, an isopropanol solution, a n-butanol solution and a dimethyl sulfoxide solution; The coating of humic acid aqueous solution comprises: A humic acid aqueous solution with a concentration of 0.2-10 mg / ml is obtained and spin-coated on the surface of the perovskite light-absorbing layer at a speed of 2000-5000 r / min for 20-60 s.

10. The method for preparing a perovskite solar cell according to claim 4 or 7, characterized in that: The perovskite light-absorbing layer includes methylamine lead iodine, formamidine lead iodine, methylamine lead bromide, formamidine lead bromide, cesium lead iodine, cesium lead bromide, methylamine tin iodine, methylamine tin bromide and a composite thereof.